Dosimetric analysis of rhizophora‑based phantom material in radiation therapy applications using Monte Carlo GATE simulation - Zuber, Siti Hajar; Abdul Hadi, Muhammad Fahmi Rizal; Samson, Damilola Oluwafemi; Jayamani, Jayapramila; Rabaiee, Nor Ain; Abdul Aziz, Mohd Zahri; Ab. Aziz, Nurul Hashikin; Ying, Chee Keat; Mohd Yusof, Mohd Fahmi; Hashim, Rokiah (Wolters Kluwer Health, 2023)
Purpose: This study aims to determine the percentage depth dose (PDD) of a phantom material made from soy‑lignin bonded Rhizophora spp. particleboard coated with a gloss finish by using Monte Carlo Geant4 Application for Tomographic Emission (GATE) simulation.